2022
DOI: 10.1128/spectrum.00862-22
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Drug Bleomycin Shows Potent Antifungal Activity by Altering Phospholipid Biosynthesis

Abstract: Invasive fungal pathogens cause significant morbidity and mortality, with over 1.5 million deaths annually. Because fungi are eukaryotes that share much of their cellular machinery with the host, our armamentarium of antifungal drugs is highly limited, with only three classes of antifungal drugs available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Bleomycin is an FDA‐approved anticancer drug widely utilized for the treatment of head and neck cancer, testicular cancer, cervical cancer, uterine cancer, and other malignancies [43,44] . This clearly indicates that the CS‐AgNPs synthesized in this study could be potentially utilized as an effective anticancer agent.…”
Section: Discussionmentioning
confidence: 62%
“…Bleomycin is an FDA‐approved anticancer drug widely utilized for the treatment of head and neck cancer, testicular cancer, cervical cancer, uterine cancer, and other malignancies [43,44] . This clearly indicates that the CS‐AgNPs synthesized in this study could be potentially utilized as an effective anticancer agent.…”
Section: Discussionmentioning
confidence: 62%
“…Currently, despite the fact that PS synthase is a promising drug target, the identification of its specific inhibitors is in the early stage. Two cell-based screens were conducted to identify inhibitors of C. albicans PS synthase, but both attempts were unsuccessful [ 244 , 245 ]. One screen pinpointed the compound SB-224289.…”
Section: Cell Membrane Biosynthesis Enzymesmentioning
confidence: 99%
“…However, it was later determined that SB-224289 only acts on PS synthase-related physiological pathways rather than the enzyme directly [ 244 ]. The other screen identified bleomycin, but it was also found that this compound affects phospholipid-associated processes rather than targeting C. albicans PS synthase directly [ 245 ]. Recently, Zhou et al identified a molecule, CBR-5884 ( Table 3 ), that inhibits both purified PS synthase and its function in vivo, with a K i of 1550 ± 245.6 nM [ 121 ].…”
Section: Cell Membrane Biosynthesis Enzymesmentioning
confidence: 99%
“…On the contrary, small-molecule screening is an alternative way to identify inhibitors to Cho1 independent of structural information. Two whole-cell screens have been carried out to identify Cho1 inhibitors, but neither has been successful ( 45 , 46 ). One identified the compound SB-224289, but it was discovered that SB-224289 only affects Cho1-associated physiological pathways ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…One identified the compound SB-224289, but it was discovered that SB-224289 only affects Cho1-associated physiological pathways ( 45 ). The other screen identified bleomycin, but this again impacts phospholipid-related physiologies rather than Cho1 itself ( 46 ). Thus, to carry out identification of a Cho1 inhibitor, a target-based screen was developed.…”
Section: Introductionmentioning
confidence: 99%